2012
DOI: 10.1111/j.1742-4658.2012.08620.x
|View full text |Cite
|
Sign up to set email alerts
|

Human MUS81 complexes stimulate flap endonuclease 1

Abstract: The yeast heterodimeric Mus81-Mms4 complex possesses a structure-specific endonuclease activity that is critical for the restart of stalled replication forks and removal of toxic recombination intermediates. Previously, we reported that Mus81-Mms4 and Rad27 (yeast FEN1, another structure-specific endonuclease) showed mutual stimulation of nuclease activity. In this study, we investigated the interactions between human FEN1 and MUS81-EME1 or MUS81-EME2, the human homologs of the yeast Mus81-Mms4 complex. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…These data suggest that Mus81 works independently of Mms4 in certain instances. It is interesting to note that in mammals, Mus81 has been shown to pair with two distinct partners, Eme1 and Eme2 (Shin et al, 2012). Although no other partner as been found in budding yeast, our results raise the possibility of a second partner or that in some circumstances, Mus81 can act alone.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest that Mus81 works independently of Mms4 in certain instances. It is interesting to note that in mammals, Mus81 has been shown to pair with two distinct partners, Eme1 and Eme2 (Shin et al, 2012). Although no other partner as been found in budding yeast, our results raise the possibility of a second partner or that in some circumstances, Mus81 can act alone.…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant human MUS81–EME2 complex was purified as previously described (20,32) with the following modifications. The pET21d-MUS81/His-EME2 plasmid was transformed into Escherichia coli BL21-Codon plus (DE3) RIL (Stratagene) and cells (2 l) were grown at 30°C until an A 600 value of 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…( A ) The purification scheme used to purify the recombinant human MUS81-EME2 complex. The recombinant human MUS81-EME2 was expressed in E. coli and purified using the same procedure as reported (20,32), but modified by the introduction of two additional purification steps (see text for details). P11, Ni 2+ -NTA and heparin indicate phosphocellulose, Ni 2+ -NTA affinity and heparin column chromatography, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…RecQ DNA helicases such as Werner syndrome protein WRN and Bloom syndrome protein BLM were shown to stimulate FEN1 through physical interaction [2628]. It was also reported that MUS81-EME1 and MUS81-EME2, DNA endonucleases involved in interstrand crosslink unhooking and Holliday junction resolution, stimulate FEN1 activity [29]. …”
Section: Introductionmentioning
confidence: 99%